A Quick Route to Unique Factorization in Quadratic Orders. Issue 6 (22nd May 2021) - Pollack, Paul; Snyder, Noah
Abstract: We give a short proof—not relying on ideal classes or the geometry of numbers—of a known criterion for quadratic orders to possess unique factorization.